Is bilingualism a guarantee of bicultural identity? - Vilkienė, Loreta (Kalbotyra, 2011)
The article seeks an answer to the question whether Russians, who speak Lithuanian and can be considered bilingual, are individuals of bicultural identity or whether they remain monocultural L2 users. In other words the issue is how much Lithuanian culture is important to the respondents of the target group. The data analyzed are quantitative surveys and qualitative interviews carried out during the project “Language Usage and National Identity in Lithuanian Cities” (2007-2009, supported by the State Studies Foundation). The data of quantitative surveys were processed by the SPSS program and then analyzed, while qualitative interviews were analyzed by the method of qualitative content analysis.The data leads to the presupposition that the Russians of the three biggest cities of Lithuania not only have conserved their national identity, but also have gained features of bicultural identity. They have multicultural competencies such as the knowledge of language and behavior, competences to act in the Lithuanian cultural context and also in the context of Russian culture. For Russian respondents Lithuania and Lithuanian culture in a broad sense are important and the tendency to identify with this culture is observed. More often it is tended to dissociate from the Lithuanian culture in a proper sense, it means from Lithuanian literature, art, customs, etc., but phenomena of adoption of Lithuanian culture can also be observed. So the cultural hybridity is characteristic of the respondents but does not create any dissatisfaction. The attitude towards the Lithuanian language is absolutely positive, the respondents claim to know the language and consider speaking Lithuanian as a very important fact for a successful integration into the Lithuanian society. They are proud of the Lithuanian language and they invite to protect it. To sum up, the knowledge of the Lithuanian language affects the changes of the respondents’ cultural identity and the bilingualism in Lithuania can be considered the stimulus (not necessarily a guarantee) of bicultural identity.
Keywords: bilingualism; bicultural identity; Lithuanian; Russians in Lithuania